Fibrous coalescence filtration in treating oily wastewater: A review - Singh, Chandra Jeet; Mukhopadhyay, Samrat; Rengasamy, Raju Seenivasan (Journal of industrial textiles, 2022)
Many industries discharge oil-in-water emulsion in the waste stream, often above the permissible limit causing serious environmental hazards. Porous media such as membrane and coalescence beds are employed to treat oily wastewater. A coalescence bed filter consists of either fibrous or granular packing and is used for removing larger oil droplets less than 100 μm from secondary emulsions. Fibrous media have higher porosities and specific surface areas than coarse granular media and hence give higher oil removal efficiency. To design an efficient fibrous coalescence bed filter for treating industrial discharge, understanding the mechanism of oil separation is important. This involves the surface wettability of fibers relating to surface chemistry and roughness. Further, fiber diameter, filter bed’s height, porosity, and pore size in relation to the oil droplet size and throughput and influent oil concentration are interactive parameters that affect the efficiency of coalescence. The performance of coalescence filtration is evaluated by analyzing the oil concentrations and D50 droplet sizes in the influent and effluent. In this article, the above-mentioned subjects are comprehensively reviewed from the reported research works, which highlights the complex nature of fibrous coalescence filtration.